Positive biofilms to control surface-associated microbial communities in a broiler chicken production system - a field study - Guéneau, Virgile; Rodiles, Ana; Frayssinet, Bastien; Piard, Jean-Christophe; Castex, Mathieu; Plateau-Gonthier, Julia; Briandet, Romain (Frontiers in Microbiology, 2022)
In the One Health concept, the use of beneficial bacteria able to form positive biofilms preventing the settlement of undesirable bacteria is a promising solution to limit the use of antimicrobials in farms. However, there is a lack of field studies reporting the onset of these beneficial bacteria after application and the effects on autochthonous surface microbiota. In this study, the inner surfaces of commercial broiler chicken houses were treated or not after cleaning and disinfection procedures with a bacterial consortium composed of Bacillus spp. and Pediococcus spp. strains, able to form covering biofilms in different laboratory models. Preinstalled coupons were sampled over time to capture microbial biofilm dynamics on-farm surfaces. The results showed that the bacterial consortium is able to establish on the farm surfaces, modulate microbial communities and limit the implantation of Enterobacteriaceae and Enterococcaceae, two families containing potential pathogens.